Stories I only tell my friends [compact disc, unabridged] : an autobiography - Lowe, Rob (Macmillan Audiobook, 2011)
A teen idol at fifteen, an international icon and founder of the Brat Pack at twenty, and one of Hollywood's top stars to this day, Rob Lowe chronicles his experiences as a painfully misunderstood child actor in Ohio uprooted to the wild counterculture of mid-seventies Malibu, where he embarked on his unrelenting pursuit of a career in Hollywood.